Method for producing conductive polymer-containing liquid and method for producing conductive laminate
By polymerizing π-conjugated conductive polymer and polycarbonate in an aqueous medium and reducing the molecular weight of polycarbonate at high temperatures, the problem of insufficient conductivity of the conductive layer is solved, and a high-conductive conductive composite film is achieved efficiently.
Patent Information
- Application Number
- JP2021203040
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-15
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2041-12-15
AI Technical Summary
In the prior art, when manufacturing a conductive composite film, the conductive layer has insufficient conductivity and a complex production process, making it difficult to achieve efficient manufacturing.
By polymerizing the π-conjugated conductive polymer with the polycarbonate in an aqueous medium, the molecular weight average molecular weight of the polycarbonate is reduced, and heated for a long time at high temperature to further reduce the molecular weight to form a conductive composite film.
The high conductivity and low surface resistance of the conductive layer are achieved, simplifying the production process and improving manufacturing efficiency.
Smart Images

Figure 0007661210000001 
Figure 0007661210000002 
Figure 0007661210000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a conductive polymer-containing liquid that contains a π-conjugated conductive polymer, and a method for producing a conductive laminate. [Background technology]
[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anion group, and becomes dispersible in water. A conductive film having a conductive layer can be manufactured by applying a conductive polymer-containing liquid (sometimes called a conductive polymer dispersion) containing the conductive complex to a film substrate or the like. In addition, an epoxy compound may be reacted with the conductive complex in order to increase the wettability of the conductive polymer-containing liquid to the film substrate or to increase the conductivity of the conductive layer to be formed. For example, Patent Document 1 discloses a method of improving the conductivity of a conductive complex by reacting a cyclic epoxy compound. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-111650 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a method for producing a conductive laminate having a conductive layer with improved conductivity, and a method for producing a conductive polymer-containing liquid used in the production method. [Means for solving the problem]
[0005] [1] A method for producing a conductive polymer-containing liquid, comprising: a polymerization step of polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion and an aqueous dispersion medium to obtain a conductive polymer-containing liquid containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the polyanion that does not form the conductive complex; and a molecular weight reduction step of reducing a weight average molecular weight of the polyanion that does not form the conductive complex and is contained in the conductive polymer-containing liquid, wherein a molecular weight ratio represented by Y / X, of the weight average molecular weight X of the polyanion that does not form the conductive complex and is contained in the conductive polymer-containing liquid subjected to the molecular weight reduction step, and the weight average molecular weight Y of the polyanion that does not form the conductive complex and is contained in the conductive polymer-containing liquid after the molecular weight reduction step, is 0.85 or less. [2] The method for producing a conductive polymer-containing liquid according to [1], wherein the molecular weight ratio is 0.60 or more and 0.85 or less. [3] The method for producing a conductive polymer-containing liquid according to [1] or [2], wherein in the molecular weight reduction step, the conductive polymer-containing liquid is heat-treated at 40° C. or higher for 400 hours or more. [4] The method for producing a conductive polymer-containing liquid according to any one of [1] to [3], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) or the polyanion is polystyrenesulfonic acid. [5] The method for producing a conductive polymer-containing liquid according to any one of [1] to [4], wherein the polyanion is polystyrene sulfonic acid, and the weight average molecular weight Y of the polystyrene sulfonic acid is 50,000 or more and 600,000 or less. [6] The method for producing a conductive polymer-containing liquid according to any one of [1] to [5], comprising adding an epoxy compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step, and obtaining a conductive polymer-containing liquid containing the obtained reaction product and an organic solvent. [7] The method for producing a conductive polymer-containing liquid according to any one of [1] to [5], comprising adding an amine compound or a quaternary ammonium compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step, and obtaining a conductive polymer-containing liquid containing the obtained reaction product and an organic solvent. [8] The method for producing a conductive polymer-containing liquid according to any one of [1] to [5], comprising adding an epoxy compound, and an amine compound or a quaternary ammonium compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step, and obtaining a conductive polymer-containing liquid containing the obtained reaction product and an organic solvent. [9] A method for producing a conductive laminate, comprising: obtaining a conductive polymer-containing liquid by the production method according to any one of [1] to [8]; and applying the conductive polymer-containing liquid to at least a part of a surface of a substrate.
[10] The method for producing a conductive laminate according to [9], wherein the substrate is a film substrate. Effect of the Invention
[0006] According to the method for producing a conductive laminate of the present invention, a conductive laminate having a conductive layer with excellent conductivity can be easily produced. According to the method for producing a conductive polymer-containing liquid of the present invention, the above-mentioned conductive polymer-containing liquid can be easily produced.
[0007] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."
[0008] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Method for producing conductive polymer-containing liquid> A first aspect of the present invention is a conductive polymer-containing liquid that includes a polymerization step and a molecular weight reduction step. The polymerization step is a step of polymerizing a monomer that forms a π-conjugated conductive polymer in a reaction liquid containing a polyanion and an aqueous dispersion medium, thereby obtaining a conductive polymer-containing liquid that contains a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the polyanion that does not form the conductive complex (hereinafter, may be referred to as a "single polyanion"). The molecular weight reduction step is a step of reducing the weight average molecular weight of the single polyanion contained in the conductive polymer-containing liquid obtained in the polymerization step. The molecular weight ratio, expressed as Y / X, of the weight average molecular weight X of the sole polyanion contained in the conductive polymer-containing liquid subjected to the molecular weight reduction step to the weight average molecular weight Y of the sole polyanion contained in the conductive polymer-containing liquid after the molecular weight reduction step is 0.85 or less. The conductive layer formed from the conductive polymer-containing liquid obtained in this embodiment has an excellent conductivity and a reduced surface resistance value due to the molecular weight ratio (Y / X) of 0.85 or less.
[0010] From the viewpoint of further increasing the conductivity of the conductive layer and further decreasing the surface resistance value, the molecular weight ratio (Y / X) is preferably from 0.60 to 0.85, more preferably from 0.65 to 0.80, and even more preferably from 0.70 to 0.75. When the content is equal to or greater than the lower limit of the above range, the conductivity of the conductive layer can be increased while suppressing gelation of the conductive polymer-containing liquid. When the content is equal to or less than the upper limit of the above range, the conductivity of the conductive layer can be further increased.
[0011] In this specification and claims, the molecular weight ratio (Y / X) has two significant digits. For example, the calculated value of Y / X=81,000 / 96,000, 0.84375, is rounded off to the third decimal place to 0.84. Here, the significant digits of each weight average molecular weight may be two digits.
[0012] In the conductive polymer-containing liquid of this embodiment, the conductive complex may be in a dispersed state or a dissolved state. In this specification, unless otherwise specified, no distinction is made between the dispersed state and the dissolved state.
[0013] <Polyanion> A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer and can improve the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. These may be homopolymers or copolymers of two or more kinds. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The polyanion may be of one type or of two or more types.
[0014] The weight average molecular weight (Mw) of the polyanion to be subjected to the polymerization step is preferably from 80,000 to 1,000,000, more preferably from 100,000 to 800,000, and even more preferably from 150,000 to 600,000. Here, the weight average molecular weight is the average molecular weight based on mass (which may also be called mass average molecular weight) measured by gel permeation chromatography (GPC) using pullulan of known weight average molecular weight as the standard substance. When the weight average molecular weight is in the above preferred range, the conductivity of the conductive layer is further increased. Before subjecting the aqueous solution of the polyanion to GPC, it is filtered through a membrane filter having an average pore size of 0.2 μm in order to remove impurities contained in the aqueous solution, and the filtrate is subjected to GPC measurement.
[0015] As a method for synthesizing a polyanion with a specific weight-average molecular weight, for example, a method of adjusting the amount of an oxidizing agent added to polymerize the monomers constituting the polyanion can be mentioned. Specifically, by increasing the concentration of the oxidizing agent, the weight-average molecular weight of the polyanion formed by polymerization of the monomers can be reduced. By this method, for example, polystyrene sulfonic acid with a weight-average molecular weight Mw of 100,000 to 1,000,000 can be obtained.
[0016] A conductive complex is formed by doping a polyanion into a π-conjugated conductive polymer. However, in the polyanion, some anion groups are not doped into the π-conjugated conductive polymer, and there are excess anion groups that are not involved in the doping. Since these excess anion groups are hydrophilic groups, the conductive complex has high water dispersibility and low organic solvent dispersibility. When the number of all anionic groups in the polyanion forming the conductive complex is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.
[0017] <π-conjugated conductive polymers> The π-conjugated conductive polymer is not particularly limited as long as it has the effect of the present invention and is an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0018] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among the above-mentioned π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable from the viewpoints of conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0019] [Polymerization process] A reaction solution containing a monomer forming the π-conjugated conductive polymer and the polyanion at an arbitrary content ratio is prepared, and the monomer is polymerized to form a π-conjugated conductive polymer. In the reaction solution, the polyanion naturally dopes the π-conjugated conductive polymer, forming a conductive complex consisting of the π-conjugated conductive polymer and the polyanion.
[0020] A catalyst may be added to the reaction solution. The catalyst is not particularly limited as long as it promotes the polymerization of the monomer, and examples thereof include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Among them, it is preferable to use a catalyst containing iron, since the polymerization of the monomer proceeds stably at room temperature.
[0021] The reaction liquid preferably contains an oxidizing agent together with the catalyst. The oxidizing agent is capable of polymerizing the monomer. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate. It is preferable that the oxidizing agent is dissolved in ion-exchanged water in advance as an oxidizing agent solution, and the oxidizing agent solution is slowly added to the mixed liquid S1 containing the monomer, the polyanion, and the catalyst to initiate polymerization. The concentration of the oxidizing agent solution is preferably 1.0% by mass or more and 3.0% by mass or less. When the volume of the mixed solution S1 before the addition of the oxidant solution is V1 and the volume of the oxidant solution is V2, the volume ratio represented by V1 / V2 is preferably 1.0 to 2.0, and more preferably 1.2 to 1.5. When the entire oxidant solution is added to the mixed solution S1, the time required from the start of addition to the end of addition is preferably 1 to 8 hours, more preferably 2 to 7 hours, and even more preferably 3 to 6 hours. The temperature of the mixed solution S1 before the addition of the oxidant solution and the temperature of the oxidant solution are each preferably 5 to 30°C independently.
[0022] The temperature of the reaction liquid obtained after the completion of the addition of all of the oxidizing agent solution is preferably kept at 5 to 30° C. while carrying out the polymerization reaction. The reaction time required for the reaction in the reaction solution to be completed is approximately 4 to 12 hours, and the reaction is preferably completed within 6 to 10 hours. The completion of the polymerization reaction can be confirmed by confirming by gas chromatography that the monomers forming the π-conjugated conductive polymer have disappeared.
[0023] The content ratio of the monomer to the polyanion contained in the mixed solution S1 is preferably from (1:2) to (1:5) on a mass basis, more preferably from (1:2) to (1:4), and even more preferably from (1:2) to (1:3). When the content is at least the lower limit of the above range, the doping effect of the polyanion is sufficiently exhibited, and the dispersion stability of the conductive composite is further improved. When the content is equal to or less than the upper limit of the above range, a conductive polymer-containing liquid capable of forming a conductive layer having excellent conductivity can be easily obtained, and a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0024] The content of the monomer relative to the total mass of the mixed liquid S1 is, for example, preferably from 0.1% by mass to 10% by mass, more preferably from 0.2% by mass to 5.0% by mass, and further preferably from 0.3% by mass to 1.0% by mass. Within the above range, the polymerization reaction can be stably carried out, and the formation of a complex with the polyanion present in the reaction system can be easily promoted. Also, a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0025] The content of the polyanion relative to the total mass of the mixed solution S1 is preferably set based on the content ratio relative to the monomer, and is, for example, preferably 0.1% by mass to 10% by mass, more preferably 0.3% by mass to 8.0% by mass, and even more preferably 0.6% by mass to 4.0% by mass. When the content is within the above range, a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0026] The weight average molecular weight of the polyanion contained in the mixed solution S1 is preferably within the above-mentioned range. When the content is within the above range, a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0027] The content of the catalyst relative to the total mass of the reaction liquid after all the oxidizing agent has been added is, for example, preferably 0.001 mass% or more and 2.0 mass% or less, more preferably 0.01 mass% or more and 1.0 mass% or less, and even more preferably 0.1 mass% or more and 0.5 mass% or less, relative to the total mass of the reaction liquid. Within the above range, the polymerization reaction can be stably carried out, and the formation of a complex with a polyanion can be easily carried out, and a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0028] The amount of the oxidizing agent added relative to the total mass of the reaction liquid after all the oxidizing agent has been added is, for example, preferably 0.01 mass% or more and 2.0 mass% or less, more preferably 0.1 mass% or more and 1.5 mass% or less, even more preferably 0.5 mass% or more and 1.2 mass% or less, and particularly preferably 0.7 mass% or more and 1.0 mass% or less. Within the above range, the polymerization reaction can be stably carried out, and the formation of a complex with a polyanion can be easily carried out, and a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0029] The amount of the monomer added before the reaction relative to the total mass of the reaction liquid after all the oxidizing agent has been added is, for example, preferably 0.05 mass% or more and 5.0 mass% or less, more preferably 0.1 mass% or more and 3.0 mass% or less, and even more preferably 0.2 mass% or more and 2.0 mass% or less. Within the above range, the polymerization reaction can be stably carried out, and the formation of a complex with the polyanion present in the reaction system can be easily promoted. Also, a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0030] The amount of the polyanion added before the reaction relative to the total mass of the reaction solution after all of the oxidizing agent has been added is, for example, preferably 0.1 mass% or more and 10 mass% or less, more preferably 0.3 mass% or more and 6.0 mass% or less, and even more preferably 0.5 mass% or more and 4.0 mass% or less. When the content is within the above range, a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained.
[0031] The aqueous dispersion medium constituting the reaction liquid contains at least water, and may further contain a water-soluble organic solvent. Specific examples of the water-soluble organic solvent will be described later. The water content relative to the total mass of the aqueous dispersion medium is, for example, preferably 60% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, even more preferably 80% by mass or more and 100% by mass or less, and particularly preferably 90% by mass or more and 100% by mass or less.
[0032] (Catalyst and oxidant removal) When a reaction liquid to which a catalyst and an oxidizing agent have been added is used, it is preferable to remove the catalyst and the oxidizing agent from the conductive polymer-containing liquid obtained after the reaction. Examples of the removal method include a method of contacting a conductive polymer-containing liquid with an ion exchange resin to adsorb the catalyst and oxidizing agent to the ion exchange resin, and a method of ultrafiltrating the conductive polymer-containing liquid to replace the aqueous dispersion medium and remove the catalyst and oxidizing agent. Among these, the method using an ion exchange resin is preferable because it is simple. It is preferable to use a cation exchange resin and an anion exchange resin in combination as the ion exchange resin.
[0033] (Distributed Processing) Before being subjected to the next molecular weight reduction step, it is preferable to stir the conductive polymer-containing liquid obtained in the polymerization step and perform a dispersion treatment of the conductive composite. The stirring method is not particularly limited, and stirring with a weak shear force such as a stirrer or stirring with a dispersing machine with a high shear force such as a high-pressure homogenizer may be used, but from the viewpoint of improving dispersibility, it is preferable to use a high-pressure homogenizer or the like.
[0034] By the above polymerization process, a conductive polymer-containing liquid is obtained, which contains a conductive complex containing a π-conjugated conductive polymer and a polyanion, the aqueous dispersion medium, and the polyanion (single polyanion) that does not form the conductive complex.
[0035] It is preferable to separate a single polyanion from the obtained conductive polymer-containing liquid and then measure its weight-average molecular weight X, since this allows accurate measurement without being affected by the conductive complex. The separation method may, for example, be a method in which the conductive polymer-containing liquid is filtered using a membrane filter having an average pore size of 0.2 μm, and the conductive complex is trapped in the filter, while the single polyanion is allowed to permeate and is recovered in the filtrate.
[0036] The weight average molecular weight X of a single polyanion is the mass average molecular weight measured by gel permeation chromatography using pullulan of known weight average molecular weight as a standard.
[0037] The weight average molecular weight X of the single polyanion is preferably smaller than the weight average molecular weight Z of the polyanion subjected to the polymerization step. The ratio of the weight average molecular weight X to the weight average molecular weight Z, expressed as X / Z, can be, for example, 0.1 or more and less than 0.67.
[0038] The weight average molecular weight X of a single polyanion is preferably from 80,000 to 800,000, more preferably from 90,000 to 700,000, and even more preferably from 95,000 to 600,000. When the ratio is equal to or greater than the lower limit of the above range, the conductivity of the conductive layer formed from the conductive polymer-containing liquid can be increased while suppressing gelation of the conductive polymer-containing liquid, and a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained. When it is equal to or less than the upper limit of the above range, the dispersibility of the polyanion in the conductive polymer-containing liquid is increased, and the conductivity of the conductive layer can be further increased.
[0039] [Low molecular weight process] In this step, the weight average molecular weight of the polyanion (single polyanion) that is not included in the conductive complex and is contained in the conductive polymer-containing liquid obtained in the polymerization step is reduced. As a method for reducing the weight average molecular weight of the single polyanion, for example, a method of heat-treating the conductive polymer-containing liquid can be mentioned. Heat treatment breaks down a portion of the molecular chain of the single polyanion, forming a polyanion with a shorter molecular chain.
[0040] The lower limit of the temperature for the heat treatment in this step is preferably not less than 40° C., more preferably not less than 50° C., and even more preferably not less than 60° C. By carrying out the heat treatment at 40° C. or higher, the efficiency of decomposing a single polyanion into smaller molecules is increased. The upper limit of the temperature for the heat treatment is preferably not more than 100° C., more preferably not more than 90° C., and even more preferably not more than 80° C. By heating at not more than 100° C., decomposition of the conductive composite can be suppressed.
[0041] The lower limit of the heat treatment time in this step is preferably 400 hours or more, more preferably 600 hours or more, even more preferably 800 hours or more, and most preferably 1000 hours or more, in the above-mentioned preferred heating temperature range. By carrying out the heat treatment for 400 hours or more, a single polyanion can be sufficiently decomposed into smaller molecular weight compounds. The upper limit of the heat treatment time is preferably 3000 hours or less, more preferably 2500 hours or less, and even more preferably 2000 hours or less, in the above-mentioned preferred heating temperature range. By carrying out the heat treatment at or below the above-mentioned upper limit, gelation of the conductive polymer-containing liquid can be reduced, and the conductive composite can be maintained in a dispersed state suitable for coating. After the heat treatment, the material is allowed to naturally cool down to the original room temperature (20 to 25° C.).
[0042] It is preferable to separate a single polyanion from the conductive polymer-containing liquid that has been subjected to the heat treatment and then measure its weight-average molecular weight Y, since this allows accurate measurement without being affected by the conductive complex. Separation of a single polyanion can be performed in the same manner as described above.
[0043] The weight average molecular weight Y of a single polyanion is the mass average molecular weight measured by gel permeation chromatography using pullulan of known weight average molecular weight as a standard substance.
[0044] The weight average molecular weight Y of a single polyanion tends to become lower as the heat treatment temperature is increased, and tends to become lower as the heat treatment time is extended.
[0045] The weight average molecular weight Y of the single polyanion is preferably from 50,000 to 600,000, more preferably from 60,000 to 500,000, and even more preferably from 70,000 to 400,000. When the ratio is equal to or greater than the lower limit of the above range, the conductivity of the conductive layer formed from the conductive polymer-containing liquid can be increased while suppressing gelation of the conductive polymer-containing liquid, and a conductive polymer-containing liquid having a desired Y / X ratio can be easily obtained. When it is equal to or less than the upper limit of the above range, the dispersibility of the polyanion in the conductive polymer-containing liquid is increased, and the conductivity of the conductive layer can be further increased.
[0046] The conductive polymer-containing liquid obtained in this step may be used as it is, or may be used after being subjected to the above-mentioned dispersion treatment. The content of the π-conjugated conductive polymer relative to the total mass of the conductive polymer-containing liquid obtained in this step can be, for example, from 0.1% by mass to 2.0% by mass. The total content of polyanions relative to the total mass of the conductive polymer-containing liquid obtained in this step can be, for example, 0.3 mass% or more and 10 mass% or less, inclusive, regardless of whether the polyanions form a conductive complex or not. The content ratio of the π-conjugated conductive polymer and the polyanion in the conductive polymer-containing liquid obtained in this step is preferably (1:2) to (1:5) on a mass basis, more preferably (1:2) to (1:4), and even more preferably (1:2) to (1:3). Here, there is no distinction between polyanions that form a conductive complex and those that do not. According to the above-described preferred embodiment, a conductive polymer-containing liquid capable of forming a conductive layer having excellent conductivity can be easily obtained.
[0047] The conductive polymer-containing liquid obtained in the above-mentioned molecular weight reduction step may be subjected to the following precipitation and recovery step or the like to modify the polyanion and make it hydrophobic.
[0048] [Precipitation recovery process] By adding at least one selected from epoxy compounds, amine compounds, and quaternary ammonium compounds to the conductive polymer-containing liquid (hereinafter, sometimes referred to as conductive polymer dispersion liquid) containing the aqueous dispersion medium obtained in the molecular weight reduction process, a reaction product containing the conductive complex can be precipitated. In addition, polyanions that do not form a conductive complex also react and precipitate in the same manner. The anion groups such as sulfonic acid groups of the reaction product precipitated in this step react with the added compound to form any one of the following substituents (A) to (C) and are hydrophobized.
[0049] The excess anionic groups of the polyanion that are not involved in the dope are hereinafter sometimes referred to as "a portion of the anionic groups". The following substituent (A) is formed by the reaction of a portion of the anion group with an epoxy compound. The following substituent (B) is formed by the reaction of a part of the anion group with an amine compound. The reaction of some anionic groups with quaternary ammonium compounds forms the following substituent (C):
[0050] (Substituent A) The substituent (A) is presumed to be a group represented by the following formula (A1) or a group represented by the following formula (A2).
[0051] [ka]
[0052] [In formula (A1), R 1 , R 2 , R 3 , and R 4 are each independently a hydrogen atom or any substituent.
[0053] [ka]
[0054] [In formula (A2), m is an integer of 2 or more, 5 , multiple R 6 , multiple R 7 , and multiple R 8 are each independently a hydrogen atom or an arbitrary substituent, and multiple R 5 may be the same or different, and multiple R 6 may be the same or different, and multiple R 7 may be the same or different, and multiple R 8 may be the same or different.]
[0055] In formulae (A1) and (A2), the bond at the left end represents that the substituent (A) is substituted with a proton of an anion group such as a sulfonic acid group.
[0056] In formula (A1), R 1 , R 2 , R 3 , and R 4 Examples of the optional substituent of R include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. 1 and R 3 may be bonded to form a ring which may have a substituent. For example, R 1 and R 3 and R 1 and a divalent hydrocarbon group obtained by removing any one hydrogen atom from the monovalent hydrocarbon group of R 3 and a divalent hydrocarbon group obtained by removing any one hydrogen atom from the monovalent hydrocarbon group above, are bonded to each other at the carbon atoms from which the hydrogen atom has been removed to form a ring. In formula (A2), R 5 , R 6 , R 7 , and R 8Examples of the optional substituent of R include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. 5 and R 7 and may be bonded to form a ring which may have a substituent. Examples of the ring are the same as those mentioned above. Here, the term "optionally having a substituent" includes both cases where a hydrogen atom (-H) is replaced with a monovalent group and cases where a methylene group (-CH2-) is replaced with a divalent group. Examples of monovalent groups as substituents include alkyl groups having 1 to 4 carbon atoms, alkenyl groups having 2 to 4 carbon atoms, halogen atoms (such as fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms), and trialkoxysilyl groups (such as trimethoxysilyl groups). Examples of the divalent group as a substituent include an oxygen atom (-O-), -C(=O)-, and -C(=O)-O-. m is an integer of 2 or more, preferably 2 to 100, more preferably 2 to 50, and even more preferably 2 to 25. When m is equal to or more than the lower limit, the hydrophobicity of the conductive composite is sufficiently high. When m is equal to or less than the upper limit, it is possible to prevent the hydrophobicity from becoming too high or the conductivity from decreasing.
[0057] The epoxy compound is a compound having one or more epoxy groups in one molecule (an epoxy group-containing compound). From the viewpoint of preventing aggregation or gelation, the epoxy compound is preferably a compound having one epoxy group in one molecule. The epoxy compound that reacts with the part of the anionic groups may be one type or two or more types.
[0058] Examples of monofunctional epoxy compounds having one epoxy group per molecule include ethylene oxide, propylene oxide, 2,3-butylene oxide, isobutylene oxide, 1,2-butylene oxide, 1,2-epoxyhexane, 1,2-epoxyheptane, 1,2-epoxypentane, 1,2-epoxyoctane, 1,2-epoxydecane, 1,3-butadiene monoxide, 1,2-epoxytetradecane, glycidyl methyl ether, 1,2-epoxyoctadecane, 1,2-epoxyhexadecane, and ethylene oxide. glycidyl ether, glycidyl isopropyl ether, tert-butyl glycidyl ether, 1,2-epoxyeicosane, 2-(chloromethyl)-1,2-epoxypropane, glycidol, epichlorohydrin, epibromohydrin, butyl glycidyl ether, 1,2-epoxyhexane, 1,2-epoxy-9-decane, 2-(chloromethyl)-1,2-epoxybutane, 2-ethylhexyl glycidyl ether, 1,2-epoxy-1H,1H,2H,2H,3H,3H-trifluorobutane, allyl glycidyl ether, tetracyanoethylene oxide, glycidyl butyrate, 1,2-epoxycyclooctane, glycidyl methacrylate, 1,2-epoxycyclododecane, 1-methyl-1,2-epoxycyclohexane, 1,2-epoxycyclopentadecane, 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 1,2-epoxy-1H,1H,2H,2H,3H,3H-heptadecafluorobutane, 3,4-epoxytetrahydrofuran, glycidyl stearate, 3-glycidyloxypropyl trimer Epoxysilane, epoxysuccinic acid, glycidyl phenyl ether, isophorone oxide, α-pinene oxide, 2,3-epoxynorbornene, benzyl glycidyl ether, diethoxy(3-glycidyloxypropyl)methylsilane, 3-[2-(perfluorohexyl)ethoxy]-1,2-epoxypropane, 1,1,1,3,5,5,5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane, 9,10-epoxy-1,5-cyclododecadiene, glycidyl 4-tert-butylbenzoate, 2,2-Bis(4-glycidyloxyphenyl)propane, 2-tert-butyl-2-[2-(4-chlorophenyl)]ethyloxirane, styrene oxide, glycidyl trityl ether, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-phenylpropylene oxide, cholesterol-5α,6α-epoxide, stilbene oxide, p-toluenesulfonic acid glycidyl, 3-methyl-3-phenylglycidic acid ethyl, N-propyl-N-(2,3-epoxypropyl)perfluoro-n- Examples of the glycidyl ethers include octyl sulfonamide, (2S,3S)-1,2-epoxy-3-(tert-butoxycarbonylamino)-4-phenylbutane, (R)-glycidyl 3-nitrobenzenesulfonate, glycidyl 3-nitrobenzenesulfonate, parthenolide, N-glycidylphthalimide, endrin, dieldrin, 4-glycidyloxycarbazole, 7,7-dimethyloctanoic acid [oxiranylmethyl], 1,2-epoxy-4-vinylcyclohexane, and higher alcohol glycidyl ethers having 10 to 16 carbon atoms.
[0059] The higher alcohol glycidyl ether is preferably at least one type of higher alcohol glycidyl ether having 10 to 16 carbon atoms, more preferably at least one type of higher alcohol glycidyl ether having 12 to 14 carbon atoms, and further preferably at least one type of C12 (12 carbon atoms) higher alcohol glycidyl ether and C13 (13 carbon atoms) higher alcohol glycidyl ether.
[0060] Examples of polyfunctional epoxy compounds having two or more epoxy groups in one molecule include 1,6-hexanediol diglycidyl ether, 1,7-octadiene diepoxide, neopentyl glycol diglycidyl ether, 4-butanediol diglycidyl ether, 1,2:3,4-diepoxybutane, 1,2-cyclohexanedicarboxylate diglycidyl, triglycidyl isocyanurate, neopentyl glycol diglycidyl ether, 1,2:3,4-diepoxybutane, polyethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and the like. Examples of the glycidyl ether include glycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane polyglycidyl ether, hydrogenated bisphenol A diglycidyl ether, hexahydrophthalic acid diglycidyl ester, glycerin polyglycidyl ether, diglycerin polyglycidyl ether, polyglycerin polyglycidyl ether, sorbitol-based polyglycidyl ether, and ethylene oxide lauryl alcohol glycidyl ether.
[0061] Since the epoxy compound has high dispersibility in organic solvents, the molecular weight is preferably from 50 to 2000. Furthermore, since the epoxy compound has high dispersibility in low-polarity hydrocarbon solvents and ester solvents, the epoxy compound preferably has a carbon number of from 4 to 120, more preferably from 7 to 100, even more preferably from 10 to 80, and particularly preferably from 15 to 50.
[0062] (Substituent B) The substituent (B) is presumed to be a group represented by the following formula (B).
[0063] -H.N. + R 11 R 12 R 13 (B) [In formula (B), R 11 ~R 13 are each independently a hydrogen atom or a hydrocarbon group which may have a substituent, provided that R 11 ~R 13 At least one of the groups is a hydrocarbon group which may have a substituent.]
[0064] In the substituent (B), the bond at the left end is the negative charge of the anion group, for example the negative charge of the sulfonic acid group "-SO3 - " represents that the positive charge of the amine compound is bonded to the aryl group.
[0065] R in chemical formula (B) 11 ~R 13 is a hydrogen atom or a hydrocarbon group which may have a substituent. 11 ~R 13 is a substituent derived from an amine compound described later. Examples of the hydrocarbon group in the chemical formula (B) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0066] The amine compound is at least one selected from the group consisting of primary amines, secondary amines, and tertiary amines. The amine compound that reacts with the part of the anion groups may be one type or two or more types. Examples of primary amines include aniline, toluidine, benzylamine, and ethanolamine. Examples of secondary amines include diethanolamine, dimethylamine, diethylamine, dipropylamine, diphenylamine, dibenzylamine, and dinaphthylamine. Examples of tertiary amines include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine. Among the amine compounds, tertiary amines are preferred because they can increase the electrical conductivity of the conductive composite of this embodiment, and at least one of trioctylamine and tributylamine is more preferred.
[0067] In order to improve dispersibility in organic solvents, particularly in low-polarity hydrocarbon solvents and ester solvents, the amine compound preferably has a substituent on the nitrogen atom having 4 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 6 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 8 or more carbon atoms. The upper limit of the carbon number of the substituent on the nitrogen atom is not particularly limited, and taking into consideration solubility in solvents and reactivity, it is, for example, preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less. In addition, the R 11 ~R 13 The total number of carbon atoms is preferably 6 to 33, more preferably 9 to 30, and further preferably 12 to 27. The number of carbon atoms in each of the substituents on the nitrogen atom may be the same or different.
[0068] When the part of the anion groups has a substituent (A) and a substituent (B), the mass ratio represented by [substituent (A)]:[substituent (B)] (hereinafter also referred to as A / B ratio) is preferably 10:90 to 90:10, more preferably 20:80 to 80:20, and even more preferably 25:75 to 75:25. When the A / B ratio is within the above range, it is easy to balance the dispersibility and the conductivity. The mass of [substituent (A)] can be calculated by [(mass of the reaction product A obtained by reacting an epoxy compound)-(mass of the conductive complex before reacting with the epoxy compound and the polyanion not forming the conductive complex)]. The mass of [substituent (B)] can be calculated by [(mass of the reaction product B obtained by reacting the reaction product A with an amine compound)-(mass of the reaction product A)].
[0069] (Substituent C) The substituent (C) is presumed to be a group represented by the following formula (C).
[0070] -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.
[0071] In the substituent (C), the bond at the left end is the negative charge of the anion group, for example the negative charge of the sulfonic acid group "-SO3 - " represents a bond between the ammonium salt and the positive charge of the quaternary ammonium cation.
[0072] R in chemical formula (C) 11 ~R 14 R in chemical formula (C) is a hydrocarbon group which may have a substituent. 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in the chemical formula (C) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0073] In order to improve dispersibility in organic solvents and conductivity, the quaternary ammonium compound preferably has a substituent on the nitrogen atom having 3 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 5 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 7 or more carbon atoms. The upper limit of the carbon number of each substituent on the nitrogen atom is not particularly limited, and taking into consideration solubility in solvents and reactivity, it is, for example, preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. In addition, the R 11 ~R 14 The total number of carbon atoms is preferably 8 to 44, more preferably 12 to 40, and further preferably 16 to 36. The number of carbon atoms in each of the substituents on the nitrogen atom may be the same or different.
[0074] Specific examples of quaternary ammonium compounds include quaternary ammonium salts such as tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetra-n-octylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, and tetranaphthylammonium salt. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.
[0075] When the conductive complex has a substituent (A) and a substituent (C), the mass ratio represented by [substituent (A)]:[substituent (C)] (hereinafter also referred to as A / C ratio) is preferably 10:90 to 90:10, more preferably 20:80 to 80:20, and even more preferably 25:75 to 75:25. When the A / C ratio is within the above range, it is easy to balance the dispersibility and the conductivity. The mass of [substituent (A)] can be calculated by [(mass of reaction product A obtained by reacting with an epoxy compound)-(mass of the conductive complex before reacting with an epoxy compound and the polyanion not forming the conductive complex)]. The mass of [substituent (C)] can be calculated by [(mass of reaction product C obtained by reacting the reaction product A with a quaternary ammonium compound)-(mass of the reaction product A)].
[0076] When one or more kinds of epoxy compounds are added to the conductive polymer dispersion, the amount of the epoxy compounds added is preferably 10 parts by mass or more and 10,000 parts by mass or less, more preferably 100 parts by mass or more and 5,000 parts by mass or less, and even more preferably 500 parts by mass or more and 3,000 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer and all polyanions (including polyanions forming a conductive complex) contained in the conductive polymer dispersion. When it is at least the lower limit of the above range, the hydrophobicity of the conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted epoxy compound can be prevented. When the epoxy compound is added, heating may be performed to promote the reaction. The heating temperature is preferably 40° C. or higher and 100° C. or lower.
[0077] When one or more kinds of amine compounds are added to the conductive polymer dispersion, the amount of the amine compound added is preferably 1 part by mass or more and 10,000 parts by mass or less, more preferably 10 parts by mass or more and 5,000 parts by mass or less, and even more preferably 100 parts by mass or more and 2,000 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer and all polyanions (including polyanions forming a conductive complex) contained in the conductive polymer dispersion. When it is at least the lower limit of the above range, the hydrophobicity of the conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted amine compound can be prevented.
[0078] When one or more kinds of quaternary ammonium compounds are added to the conductive polymer dispersion, the amount of the quaternary ammonium compound added is preferably 1 part by mass or more and 10,000 parts by mass or less, more preferably 10 parts by mass or more and 5,000 parts by mass or less, and even more preferably 50 parts by mass or more and 2,000 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer and all polyanions (including polyanions forming a conductive complex) contained in the conductive polymer dispersion. When it is at least the lower limit of the above range, the hydrophobicity of the conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted quaternary ammonium compound can be prevented. The quaternary ammonium compound has a reaction mechanism similar to that of the amine compound, and shows good reactivity even with a smaller amount of addition than the amine compound. The conductivity of the conductive layer containing the conductive complex modified with the quaternary ammonium compound tends to be better than that of the conductive layer modified with the amine compound.
[0079] An organic solvent may be added before, simultaneously with, or after adding one or more selected from an epoxy compound, an amine compound, and a quaternary ammonium compound to the conductive polymer dispersion. The organic solvent is preferably a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The organic solvent to be added may be one type or two or more types.
[0080] When both the epoxy compound and the amine compound or the quaternary ammonium compound are added to the conductive polymer dispersion, the order of addition is not particularly limited. Since the synthetic intermediate (reaction intermediate) is easy to handle, it is preferable to first add the epoxy compound and react it, and then add the amine compound or the quaternary ammonium compound and react it.
[0081] The method for recovering the precipitated reaction product is not particularly limited, and the product can be recovered, for example, by filtration, decantation, or the like.
[0082] It is preferable that the water content of the recovered reaction product (precipitate) is as small as possible, and it is most preferable that it contains no water at all, but from a practical standpoint, it may contain water in the range of 10 mass % or less. Methods for reducing the water content include, for example, washing the reaction product with an organic solvent, drying the reaction product, and the like.
[0083] [Cleaning process] The method may include a washing step for washing the reaction product recovered in the precipitation recovery step, which removes residual water, unreacted epoxy compounds, unreacted amine compounds or quaternary ammonium compounds, hydrolyzates of epoxy compounds, and the like. The organic solvent for cleaning is preferably one that can clean the reaction product while minimizing dissolution of the reaction product. For this reason, the organic solvent for cleaning is preferably an alcohol-based solvent. The organic solvent for cleaning may contain one type of organic solvent or two or more types of organic solvents. The washing method is not particularly limited. For example, the reaction product may be washed by pouring an organic solvent for washing over the reaction product, or the reaction product may be washed by stirring in the organic solvent for washing.
[0084] [Addition process] This step is a step of adding a dispersion medium to the reaction product to obtain a conductive polymer-containing liquid. The dispersion medium to be added may be any medium capable of dispersing the reaction product, and preferably contains an organic solvent. When the conductive polymer-containing liquid contains a hydrophobized conductive complex, the content of the organic solvent relative to the total mass of the dispersion medium is preferably 70 mass% or more and 100 mass% or less, more preferably 80 mass% or more and 100 mass% or less, and even more preferably 90 mass% or more and 100 mass% or less.
[0085] The content of the reaction product relative to the total mass of the conductive polymer-containing liquid obtained in this step is, for example, preferably 0.01 mass % or more and 10 mass % or less, more preferably 0.1 mass % or more and 3 mass % or less, and even more preferably 0.2 mass % or more and 1 mass % or less. When the content is at least the lower limit of the above range, the conductivity of the conductive layer formed by applying the conductive polymer-containing liquid can be further improved. When the content is equal to or less than the upper limit of the above range, the dispersibility of the reaction product in the conductive polymer-containing liquid can be improved, and a uniform conductive layer can be formed.
[0086] <Organic solvent> Examples of the organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, ester-based solvents, hydrocarbon-based solvents, nitrogen atom-containing compound-based solvents, etc. The organic solvent may be one type or two or more types.
[0087] The organic solvent may be a water-soluble organic solvent or a water-insoluble organic solvent. The water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20° C., and the water-insoluble organic solvent is an organic solvent that dissolves in an amount of less than 1 g in 100 g of water at 20° C. The water-soluble organic solvent is preferably one or more selected from alcohol-based solvents.
[0088] Examples of alcohol-based solvents include monohydric alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether; and dihydric alcohols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, and 1,4-butanediol. Examples of the ether solvent include diethyl ether, dimethyl ether, and propylene glycol dialkyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the ester-based solvents and the hydrocarbon-based solvents will be described later. Examples of the nitrogen atom-containing compound solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. An example of a solvent not classified into the above categories is dimethyl sulfoxide.
[0089] (Ester solvent) The ester solvent is an ester group-containing compound having an ester group (-C(=O)-O-). When the conductive complex is modified by a reaction with an epoxy compound and an amine compound or a quaternary ammonium compound, it is preferable that the organic solvent contains an ester-based solvent, since this further enhances the dispersibility of the conductive complex. From the viewpoint of improving the dispersibility of the conductive composite, it is preferable to contain one or more ester solvents represented by the following formula 1z. Formula 1z:R 21 -C(=O)-OR 22 [In the formula, R 21 represents a hydrogen atom, a methyl group, or an ethyl group; R 22 represents a linear or branched alkyl group having 1 to 6 carbon atoms.]
[0090] From the viewpoint of improving the dispersibility of the conductive composite, R 21 is preferably a methyl group or an ethyl group, more preferably a methyl group. 22 The number of carbon atoms is preferably 2 to 5, and more preferably 2 to 4.
[0091] Examples of the ester solvent include ethyl acetate, propyl acetate, butyl acetate, isopropyl acetate, and isobutyl acetate.
[0092] The content of the ester solvent in the organic solvent is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, most preferably 90% by mass or more, and may be 100% by mass, based on the total mass of the organic solvent. When the content of the ester solvent is within the above range, the dispersibility of the conductive composite can be increased.
[0093] When the conductive polymer-containing liquid of this embodiment contains an ester-based solvent, it may further contain one or more organic solvents other than the ester-based solvent. Examples of organic solvents other than ester-based solvents include the hydrocarbon-based solvents described below, the ketone-based solvents, alcohol-based solvents, and nitrogen atom-containing compound-based solvents described above.
[0094] (Hydrocarbon solvents) In the case where the conductive complex contained in the conductive polymer-containing liquid of this embodiment is modified by a reaction with an epoxy compound and an amine compound or a quaternary ammonium compound, it is preferable to contain a hydrocarbon-based solvent as a dispersion medium, since this increases the wettability with respect to the plastic film substrate and makes it easy to add a binder component with low polarity.
[0095] Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include pentane, hexane, heptane, octane, decane, cyclohexane, and methylcyclohexane. Examples of the aromatic hydrocarbon solvent include benzene, toluene, xylene, ethylbenzene, propylbenzene, and isopropylbenzene. Among them, toluene is preferred because of its high dispersibility of the conductive composite. In addition, when a silicone compound is added as a binder component, at least one of heptane and toluene is preferred because of its excellent solubility in the silicone compound.
[0096] It is preferable to further contain methyl ethyl ketone in addition to the hydrocarbon solvent, since this further increases the dispersibility of the conductive composite. For example, the amount of methyl ethyl ketone is preferably 20 parts by mass or more and 120 parts by mass or less, more preferably 30 parts by mass or more and 100 parts by mass or less, and even more preferably 40 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the hydrocarbon solvent.
[0097] The content of the hydrocarbon solvent is preferably 40% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, most preferably 90% by mass or more, and may be 100% by mass, based on the total mass of the organic solvent. When the content of the hydrocarbon solvent is within the above range, the dispersibility of the conductive composite can be increased.
[0098] When the conductive polymer-containing liquid of this embodiment contains a hydrocarbon-based solvent, it may further contain one or more organic solvents other than the hydrocarbon-based solvent. Examples of organic solvents other than hydrocarbon solvents include the above-mentioned ketone solvents, alcohol solvents, ester solvents, and nitrogen atom-containing compound solvents.
[0099] Among the above, the organic solvent is preferably one or more selected from alcohol-based solvents, ketone-based solvents, and ester-based solvents, and more preferably one or more selected from isopropanol, methyl ethyl ton, and ethyl acetate. By using these suitable organic solvents, the dispersibility of the conductive complex contained in the conductive polymer-containing liquid can be further improved.
[0100] (Distributed Processing) After adding the dispersion medium to the reaction product, the conductive polymer-containing liquid may be stirred to carry out a dispersion treatment. The stirring method is not particularly limited, and may be a stirring method with a weak shear force such as a stirrer, or may be a stirring method with a dispersing machine with a high shear force such as a high-pressure homogenizer, but it is preferable to use a high-pressure homogenizer from the viewpoint of improving dispersibility.
[0101] (Optional ingredient addition) A binder component and other additives may be further added to the conductive polymer-containing liquid obtained as described above.
[0102] <Addition of binder components> The conductive polymer-containing liquid of this embodiment may further contain a binder component. By using a conductive polymer-containing liquid containing a binder component, the strength of the conductive layer to be formed can be improved and adhesiveness and releasability can be imparted. The binder component is a resin other than the π-conjugated conductive polymer and the polyanion or a precursor thereof, and is a thermoplastic resin, or a curable monomer or oligomer that is cured when the conductive layer is formed. The thermoplastic resin becomes the binder resin as it is, and the curable monomer or oligomer becomes the resin formed by curing. The binder component may be a pressure-sensitive adhesive, which will be described later. In this embodiment, the binder component to be added may be one type or two or more types.
[0103] Specific examples of binder resins derived from binder components include epoxy resins, acrylic resins (acrylic compounds), polyester resins, polyurethane resins, polyimide resins, polyether resins, melamine resins, and silicones.
[0104] The curable monomer or oligomer may be a thermosetting monomer or oligomer, or a photocurable monomer or oligomer. Here, the oligomer refers to a polymer having a mass average molecular weight of less than 10,000. Examples of the curable monomer include an acrylic monomer (acrylic compound), an epoxy monomer, an organosiloxane, etc. Examples of the curable oligomer include an acrylic oligomer (acrylic compound), an epoxy oligomer, a silicone oligomer (curable silicone), etc. When an acrylic monomer or an acrylic oligomer is used as the binder component, it can be easily cured by heating or irradiating with light.
[0105] When a curable monomer or oligomer is included, it is preferable to further include a curing catalyst. For example, when a thermosetting monomer or oligomer is included, it is preferable to include a thermal polymerization initiator that generates radicals by heating, and when a photocurable monomer or oligomer is included, it is preferable to include a photopolymerization initiator that generates radicals by light irradiation.
[0106] The content ratio of the binder components (excluding the silicone compound described later) contained in the conductive polymer-containing liquid of this embodiment is, for example, preferably 1 part by mass or more and 10,000 parts by mass or less, more preferably 10 parts by mass or more and 5,000 parts by mass or less, and even more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 1 part by mass of the π-conjugated conductive polymer and all polyanions. When the content is equal to or greater than the lower limit of the above range, the characteristics of the binder component contained in the conductive layer formed from the conductive polymer-containing liquid of this embodiment can be fully exhibited. When it is equal to or less than the upper limit of the above range, sufficient conductivity of the conductive layer formed from the conductive polymer-containing liquid of this embodiment can be ensured.
[0107] (Silicone compounds) When the dispersion medium of the conductive polymer-containing liquid of this embodiment contains a hydrocarbon-based solvent or an ester-based solvent, the dispersibility of the silicone compound is preferably further improved. Examples of the silicone compound include curable silicone. When the binder component is curable silicone, releasability can be imparted to the conductive layer by curing the curable silicone.
[0108] The curable silicone may be either an addition curable silicone or a condensation curable silicone. In this embodiment, the addition curable silicone is preferred because it is less likely to cause curing inhibition.
[0109] The addition curing silicone may be a linear polymer having a siloxane bond, which includes polydimethylsiloxane having vinyl groups at both ends of the linear chain, and hydrogen silane. Such addition curing silicone forms a three-dimensional crosslinked structure by addition reaction and cures. A platinum-based curing catalyst may be used to accelerate the cure. Specific examples of addition curing silicones include KS-3703T, KS-847T, KM-3951, X-52-151, X-52-6068, and X-52-6069 (manufactured by Shin-Etsu Chemical Co., Ltd.). The addition curing type silicone is preferably dissolved or dispersed in an organic solvent.
[0110] The content ratio of the silicone compound contained in the conductive polymer-containing liquid of this embodiment is preferably 10 parts by mass or more and 10,000 parts by mass or less, more preferably 100 parts by mass or more and 5,000 parts by mass or less, and even more preferably 500 parts by mass or more and 3,000 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer and the total polyanion. When the content is equal to or greater than the lower limit of the above range, sufficient releasability can be imparted to the conductive layer formed from the conductive polymer-containing liquid of this embodiment. When it is equal to or less than the upper limit of the above range, sufficient conductivity of the conductive layer formed from the conductive polymer-containing liquid of this embodiment can be ensured.
[0111] [Adhesive] The conductive polymer-containing liquid of this embodiment may contain an adhesive as a binder component. By using a conductive polymer-containing liquid containing an adhesive, a conductive layer having adhesive properties can be formed. When the dispersion medium of the conductive polymer-containing liquid of this embodiment contains a hydrocarbon-based solvent or an ester-based solvent, it can be easily mixed with a pressure-sensitive adhesive that has been dispersed in advance in a hydrocarbon-based solvent or an ester-based solvent, and the conductive complex can be stably dispersed in the mixed liquid, which is preferable.
[0112] The degree of adhesiveness of the adhesive is not particularly limited, and may be adhesive enough to be easily peeled off by hand after application, or may be adhesive enough to be difficult to peel off after application. Adhesiveness that is difficult to peel off can be rephrased as adhesiveness. In other words, the adhesiveness may be such that it is possible to adhere semi-permanently.
[0113] As the pressure-sensitive adhesive, known pressure-sensitive adhesives can be used, and from the viewpoint of exhibiting good adhesiveness while maintaining electrical conductivity, acrylic pressure-sensitive adhesives are preferred.
[0114] (Acrylic adhesive) The acrylic adhesive can bond and integrate the surfaces of the same or different solids. The acrylic adhesive contains an acrylic resin (acrylic polymer).
[0115] Specific examples of acrylic monomers that form acrylic resins include acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ditrimethylolpropane tetraacrylate, 2-hydroxy-3-phenoxypropyl acrylate, bisphenol A·ethylene oxide modified diacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, dipentaerythritol monohydroxypentaacrylate, dipropylene glycol diacrylate, trimethylolpropane triacrylate, glycerol propoxy triacrylate, 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, acrylate, isobornyl acrylate, polyethylene glycol diacrylate, pentaerythritol triacrylate, tetrahydrofurfuryl acrylate, tripropylene glycol diacrylate, and other acrylates; methacrylates, such as tetraethylene glycol dimethacrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, allyl methacrylate, 1,3-butylene glycol dimethacrylate, benzyl methacrylate, cyclohexyl methacrylate, diethylene glycol dimethacrylate, 2-ethylhexyl methacrylate, glycidyl methacrylate, 1,6-hexanediol dimethacrylate, 2-hydroxyethyl methacrylate, isobornyl methacrylate, lauryl methacrylate, phenoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, and trimethylolpropane trimethacrylate, and other methacrylates;Examples of (meth)acrylamides include diacetone acrylamide, N,N-dimethylacrylamide, dimethylaminopropyl acrylamide, dimethylaminopropyl methacrylamide, methacrylamide, N-methylolacrylamide, acryloylformolin, N-methylacrylamide, N-isopropylacrylamide, Nt-butylacrylamide, N-phenylacrylamide, acryloylpiperidine, and 2-hydroxyethylacrylamide. The acrylic resin may be formed of one type of acrylic monomer or two or more types of acrylic monomers. By combining two or more types of acrylic monomers, the adhesiveness can be adjusted.
[0116] The acrylic resin may be a copolymer of an acrylic monomer and a vinyl monomer other than the acrylic monomer. Examples of vinyl monomers include styrene, α-methylstyrene, vinyl acetate, acrylonitrile, methacrylonitrile, and maleic anhydride. The content of the acrylic monomer unit in the copolymer is preferably 50 mol % or more and less than 100 mol %, and more preferably 70 mol % or more and 98 mol % or less. When the content of the acrylic monomer unit is equal to or more than the lower limit, adhesiveness can be easily exhibited. The content of the vinyl monomer unit in the copolymer can be, for example, from 2 mol % to 20 mol %.
[0117] The glass transition temperature of the acrylic resin is preferably 80° C. or lower, more preferably 50° C. or lower, and even more preferably 0° C. or lower. An acrylic resin having a glass transition temperature of more than 80° C. has low adhesion. The glass transition temperature of an acrylic resin is −80° C. or higher, and it is difficult to obtain an acrylic resin having a glass transition temperature lower than that. The glass transition temperature of an acrylic resin can be determined by differential scanning calorimetry or dynamic viscoelasticity measurement. Examples of acrylic monomers that tend to lower the glass transition temperature of acrylic resins include ethyl acrylate, butyl acrylate (particularly n-butyl acrylate), 2-ethylhexyl acrylate, etc. In acrylic resins, the higher the ratio of these monomer units, the lower the glass transition temperature.
[0118] The mass average molecular weight of the acrylic resin is preferably 10,000 to 2,000,000, and more preferably 30,000 to 1,000,000. If the mass average molecular weight of the acrylic resin is equal to or greater than the lower limit, sufficient cohesive strength can be ensured. If the mass average molecular weight is equal to or less than the upper limit, adhesion can be further improved.
[0119] When the acrylic resin has an acrylic monomer unit having a reactive functional group, it may be cured by reacting with a curing agent. When the acrylic resin is cured, the cohesive force of the conductive layer containing the adhesive is improved, and the strength can be improved. In addition, by improving the cohesive force of the conductive layer, it is possible to make the conductive layer removably capable of repeated adhesion and peeling. Examples of the reactive functional group include a hydroxy group, a carboxy group, an amino group, an amide group, an epoxy group, etc. When reacting with a polyfunctional isocyanate described later, the reactive functional group is preferably a hydroxy group, a carboxy group, or an amino group, and more preferably a hydroxy group. Examples of acrylic monomers having a hydroxy group include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate. Examples of the acrylic monomer having a carboxy group include acrylic acid, methacrylic acid, and itaconic acid. Examples of the acrylic monomer having an amino group include dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, diethylaminoethyl acrylate, and diethylaminoethyl methacrylate. Examples of acrylic monomers having an amide group include acrylamide, methacrylamide, N-methylol acrylamide, and N-methylol methacrylamide. Examples of the acrylic monomer having an epoxy group include glycidyl acrylate and glycidyl methacrylate. When a polyfunctional isocyanate is used as a curing agent, among the acrylic monomers having a reactive functional group, taking into consideration curability and cost, an acrylic monomer having a hydroxy group is preferred, and 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate are more preferred. The acrylic monomer having a reactive functional group that forms the acrylic resin may be of one type or of two or more types.
[0120] The content of the adhesive in the conductive polymer-containing liquid of this embodiment is preferably from 10 parts by mass to 10,000 parts by mass, more preferably from 100 parts by mass to 5,000 parts by mass, and even more preferably from 300 parts by mass to 1,000 parts by mass, per part by mass of the π-conjugated conductive polymer and all polyanions. When it is equal to or greater than the lower limit of the above range, sufficient adhesion can be imparted to the conductive layer formed by the conductive polymer-containing liquid of this embodiment. When it is equal to or less than the upper limit of the above range, sufficient conductivity of the conductive layer formed from the conductive polymer-containing liquid of this embodiment can be ensured.
[0121] (hardening agent) When the adhesive contained in the conductive polymer-containing liquid of this embodiment has a reactive functional group, the conductive polymer-containing liquid of this embodiment preferably contains a curing agent. Examples of the curing agent include isocyanate-based curing agents such as polyfunctional isocyanates having two or more isocyanate groups in one molecule, and epoxy-based curing agents such as epoxy compounds having two or more epoxy groups in one molecule. Among these curing agents, polyfunctional isocyanates are preferred from the viewpoint of reactivity. In particular, when the adhesive has an acrylic monomer unit having a hydroxyl group, it is preferred that the curing agent is a polyfunctional isocyanate.
[0122] Examples of the polyfunctional isocyanate include aliphatic polyfunctional isocyanates, alicyclic polyfunctional isocyanates, and aromatic polyfunctional isocyanates. Specific examples of polyfunctional isocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, polyphenylene polymethylene polyisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, p-phenylene diisocyanate, transcyclohexane 1,4-diisocyanate, 4,4'-dicyclomethane diisocyanate, 3, Examples of the isocyanate include 3'-dimethyl-4,4'-diphenylmethane diisocyanate, dianisidine diisocyanate, m-xylylene diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, 1,4-cyclohexane diisocyanate, lysine diisocyanate, lysine ester triisocyanate, tetramethylxylene diisocyanate, 1,6,11-undecane triisocyanate, 1,3,6-hexamethylene triisocyanate, bicyclohepta triisocyanate, and trimethylhexamethylene diisocyanate. The polyfunctional isocyanate may be a modified diisocyanate formed from a modified polyfunctional isocyanate obtained by modifying the diisocyanate so that the NCO / OH molar ratio becomes 2 / 1 or more. The polyfunctional isocyanate may be a modified polyisocyanate. Examples of the modified polyisocyanate include polyurethane polyisocyanates obtained by reacting the polyfunctional isocyanate with polyhydric alcohols, polyisocyanates containing an isocyanurate ring obtained by polymerizing a polyfunctional isocyanate, and polyisocyanates containing a biuret bond obtained by reacting a polyfunctional isocyanate with water. The conductive polymer-containing liquid of this embodiment may contain one type of curing agent, or two or more types of curing agents.
[0123] The content ratio of the curing agent contained in the conductive polymer-containing liquid of this embodiment is, for example, preferably 1 part by mass or more and 100 parts by mass or less, more preferably 2 parts by mass or more and 50 parts by mass or less, and even more preferably 3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the adhesive. When the content is within the above range, sufficient adhesion can be imparted to the conductive layer formed by the conductive polymer-containing liquid of this embodiment.
[0124] (Highly conductive agent) The conductive polymer-containing liquid of this embodiment may contain a conductivity enhancing agent. Here, the above-mentioned π-conjugated conductive polymer, polyanion, organic solvent, adhesive, curing agent, and binder component are not classified as a high-conductivity agent. Note that the above-mentioned epoxy compound, amine compound, and quaternary ammonium compound may be included in the high-conductivity agent described here. The conductive agent is preferably at least one compound selected from the group consisting of saccharides, nitrogen-containing aromatic cyclic compounds, compounds having two or more hydroxyl groups, compounds having one or more hydroxyl groups and one or more carboxyl groups, compounds having an amide group, compounds having an imide group, lactam compounds, and compounds having a glycidyl group. The conductive polymer-containing liquid of this embodiment may contain one type of highly conductive agent, or two or more types of highly conductive agents. The content ratio of the conductive agent is preferably 1 part by mass or more and 10,000 parts by mass or less, more preferably 10 parts by mass or more and 5,000 parts by mass or less, and even more preferably 100 parts by mass or more and 2,500 parts by mass or less, relative to 100 parts by mass of the π-conjugated conductive polymer and the total polyanion. When the content ratio of the conductive agent is equal to or more than the lower limit, the effect of improving the conductivity by adding the conductive agent is sufficiently exhibited, and when the content ratio is equal to or less than the upper limit, a decrease in the conductivity caused by a decrease in the concentration of the π-conjugated conductive polymer can be prevented.
[0125] (Other additives) The conductive polymer-containing liquid of this embodiment may contain other known additives. The additives are not particularly limited as long as the effects of the present invention can be obtained. For example, surfactants, inorganic conductive agents, antifoaming agents, coupling agents, antioxidants, ultraviolet absorbing agents, etc. can be used. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group or an amino group. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers. When the conductive polymer-containing liquid of this embodiment contains the additive, the content ratio thereof is appropriately determined depending on the type of additive, and can be, for example, in the range of 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the π-conjugated conductive polymer and the total polyanion.
[0126] <Method for manufacturing conductive laminate> A second aspect of the present invention is a method for producing a conductive laminate, comprising the steps of obtaining a conductive polymer-containing liquid by the production method of the first aspect and applying the conductive polymer-containing liquid to at least a partial surface of a substrate.
[0127] [Base material] The substrate may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface, such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0128] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably a polyester resin, and among these, polyethylene terephthalate is preferable.
[0129] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesion of the conductive layer.
[0130] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0131] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0132] The average thickness of the glass substrate is preferably from 100 μm to 3000 μm, more preferably from 100 μm to 1000 μm. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to break, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to a thinner conductive laminate. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0133] Examples of a method for applying (coating) the conductive polymer-containing liquid on an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0134] The amount of conductive polymer-containing liquid applied to the substrate is not particularly limited, but taking into consideration uniform and even application, conductivity, and film strength, a solid content of 0.01 g / m 2 More than 10.0g / m 2 The following ranges are preferred:
[0135] The conductive layer can be formed by drying the coating film made of the conductive polymer-containing liquid applied onto the substrate to remove at least a portion of the dispersion medium and curing the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 200° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 0.5 minutes to 30 minutes, more preferably 1 minute to 15 minutes. After drying, UV irradiation may be performed to harden the binder component contained in the coating film.
[0136] The conductive layer may be formed over the entire surface of any surface of the substrate, or over a portion of the entire surface. In the conductive film, it is preferable that a conductive layer of substantially uniform thickness is formed over substantially the entire surface of one surface or the other surface of the film substrate. When a conductive layer is formed only over a portion of the surface of the substrate, the conductive layer may be, for example, a fine conductive pattern such as a circuit or an electrode, or the conductive layer may be provided on the same surface and the conductive layer may be not provided on the same surface and may be roughly divided.
[0137] The average thickness of the conductive layer is, for example, preferably 10 nm or more and 100 μm or less, more preferably 20 nm or more and 50 μm or less, and even more preferably 30 nm or more and 30 μm or less. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved. The average thickness of the conductive layer is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values. EXAMPLES
[0138] (Production Example 1) Production of polystyrene sulfonic acid 1 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid. Next, 10 g of the obtained polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous polystyrene sulfonic acid solution.
[0139] The weight-average molecular weight (Mw) of the polystyrene sulfonate (PSS) obtained above was measured by gel permeation chromatography (GPC) using pullulan of known weight-average molecular weight as the standard substance, and the weight-average molecular weight was found to be 180,000. The weight-average molecular weight was measured using a Prominence high-performance liquid chromatograph manufactured by Shimadzu Corporation, 0.1% NaNO3 aqueous solution as the solvent, a Shodex OHpack SB-806M HQ column, and a RID-20A detector, with the solvent temperature set to 40°C, the flow rate set to 0.6 ml / min, the PSS concentration in the sample set to 0.1 mass%, 100 μl of the sample filtered through a membrane filter with a pore size of 0.2 μm was injected, and the analysis software Lab Solutions (manufactured by Shimadzu Corporation) was used.
[0140] (Production Example 2) Production of polystyrene sulfonic acid 2 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 0.38 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate solution, and about 1000ml of the solvent from the obtained polystyrene sulfonic acid solution was removed by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration to wash the polystyrene sulfonic acid with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid. Next, 10 g of the obtained polystyrene sulfonic acid was dissolved in 90 g of ion-exchanged water to obtain a 10% by mass aqueous polystyrene sulfonic acid solution. The weight average molecular weight of the polystyrene sulfonic acid (PSS) obtained above, measured by GPC in the same manner as in Production Example 1, was 540,000.
[0141] Example 1 3.0 g of 3,4-ethylenedioxythiophene (EDOT), 90 g of the 10 mass % PSS aqueous solution of Production Example 1, and 325 g of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and 1.2 g of ferric sulfate was added thereto while stirring. Next, an oxidant solution (25°C) prepared by dissolving 6.6 g of sodium persulfate in 293.4 g of ion-exchanged water was slowly added over a period of 4 hours, and after the addition of all the oxidant solution was completed, the resulting reaction solution (25°C) was stirred for 8 hours to cause a reaction. By the above reaction, a conductive polymer-containing liquid was obtained that contained a conductive complex (PEDOT-PSS) containing poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid, which are π-conjugated conductive polymers, and water, which is a dispersion medium. To this conductive polymer-containing liquid, 39 g of Duolite C255LFH (manufactured by Sumika Chemtex Corporation, cation exchange resin) and 39 g of Duolite A368S (manufactured by Sumika Chemtex Corporation, anion exchange resin) were added, and the mixture was filtered to remove the ion exchange resin, thereby obtaining 710 g of conductive polymer-containing liquid (non-volatile component concentration 1.4% by mass) from which the oxidant and the catalyst had been removed. Next, ion-exchanged water was added to the obtained conductive polymer-containing liquid to adjust the non-volatile component concentration to 1.0 mass %, and the liquid was dispersed using a high-pressure homogenizer.
[0142] A portion of the conductive polymer-containing solution was taken and analyzed by gas chromatography mass spectrometry, revealing that the amount of unreacted EDOT was below the measurement limit. This result indicates that almost all of the EDOT had formed PEDOT. The above gas chromatography measurements were performed using a Shimadzu GCMS-QP2010Plus, helium as the carrier gas, a DB-5MS as the column, a secondary electron multiplier with a conversion diode as the detector, the vaporization temperature set to 250°C, the flow rate set to 1.2 mL / min, 1 μL of sample injected, the PEDOT-PSS concentration in the sample set to 1.0 mass%, and the analysis software GCMSsolution.
[0143] A portion of the conductive polymer-containing solution was taken and filtered through a membrane filter with a pore size of 0.2 μm (Membrane Solution Japan, model number: NY-030022), trapping the PEDOT-PSS on the membrane while allowing the PSS alone (not forming PEDOT-PSS) contained in the conductive polymer-containing solution to permeate and be collected in the filtrate. The weight-average molecular weight of the PSS contained in this filtrate was measured by GPC as explained in Production Example 1, and was found to be 96,000.
[0144] Next, the conductive polymer-containing liquid was heated and allowed to stand at 40°C for 720 hours, and then returned to room temperature (25°C). The weight-average molecular weight of the PSS that did not form PEDOT-PSS was measured by GPC in the same manner as above, and was found to be 81,000. Therefore, the weight average molecular weight X of the PSS alone after the polymerization step was 96,000, and the weight average molecular weight Y of the PSS alone after the molecular weight reduction step was 81,000, so Y / X was 0.84. There was no change in the properties of the conductive polymer-containing liquid (paint) before and after the above heat treatment, and PEDOT-PSS maintained dispersibility suitable for coating.
[0145] Next, the conductive polymer-containing liquid that had been subjected to the above heat treatment was applied onto a PET film using a bar coater #4, and then dried at 120° C. for 1 minute to obtain a conductive film. The surface resistance value of this conductive film was measured, and the results are shown in Table 1.
[0146] The surface resistance of the conductive layer of the conductive film was measured using a resistivity meter (Hiresta manufactured by Nitto Seiko Analytech Co., Ltd.) under the condition of an applied voltage of 10 V. In the table, "1.0E+04" means "1.0 x 10 4 " and so on.
[0147] Example 2 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 40°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0148] Example 3 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 40°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0149] Example 4 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 60°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured. After the above heat treatment, the viscosity of the conductive polymer-containing liquid (paint) had increased and it was possible to coat it, but the PEDOT-PSS was on the verge of gelling and coagulating.
[0150] Comparative Example 1 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 25°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0151] Comparative Example 2 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 25°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0152] Comparative Example 3 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 25°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0153] Comparative Example 4 A conductive polymer-containing liquid was obtained in the same manner as in Example 1, except that the heat treatment in Example 1 was changed to "standing at 40°C for 360 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0154] [Table 1]
[0155] Example 5 Except for changing "90 g of the 10 mass % PSS aqueous solution of Production Example 1 and 325 g of ion-exchanged water were mixed at 20° C." in Example 1 to "150 g of the 10 mass % PSS aqueous solution of Production Example 1 and 265 g of ion-exchanged water were mixed at 20° C.", 710 g of conductive polymer-containing liquid (non-volatile component concentration 1.8 mass %) was obtained in the same manner as in Example 1. Except for this, a conductive polymer-containing liquid was obtained, the weight average molecular weight was measured, and a conductive film was produced and its surface resistance value was measured in the same manner as in Example 1. The results are shown in Table 2.
[0156] Example 6 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 40°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0157] Example 7 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 40°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0158] Example 8 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 60°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0159] Comparative Example 5 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 25°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0160] Comparative Example 6 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 25°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0161] Comparative Example 7 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 25°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0162] Comparative Example 8 A conductive polymer-containing liquid was obtained in the same manner as in Example 5, except that the heat treatment in Example 5 was changed to "standing at 40°C for 360 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0163] [Table 2]
[0164] Example 9 Except for changing "90 g of 10 mass % PSS aqueous solution of Production Example 1" in Example 1 to "90 g of 10 mass % PSS aqueous solution of Production Example 2," 710 g of conductive polymer-containing liquid (non-volatile component concentration 1.4 mass %) was obtained in the same manner as in Example 1, the weight average molecular weight was measured, and a conductive film was produced and its surface resistance value was measured. The results are shown in Table 3.
[0165] Example 10 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 40°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0166] Example 11 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 40°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0167] Example 12 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 60°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0168] Comparative Example 9 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 25°C for 720 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0169] Comparative Example 10 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 25°C for 1440 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0170] Comparative Example 11 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 25°C for 2160 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0171] Comparative Example 12 A conductive polymer-containing liquid was obtained in the same manner as in Example 9, except that the heat treatment in Example 9 was changed to "standing at 40°C for 360 hours," and the weight average molecular weight was measured. A conductive film was produced and its surface resistance value was measured.
[0172] [Table 3]
[0173] Example 13 50g of isopropanol and 10g of trioctylamine were added to 100g of the conductive polymer-containing liquid (non-volatile component concentration 1.0% by mass) of Example 1 and stirred for 1 hour, and trioctylamine was reacted with some of the sulfonic acid groups of the conductive complex. As a result, all of the reaction product was precipitated in the upper layer of the reaction liquid. This precipitate was filtered to obtain a powder of the reaction product of the conductive complex and trioctylamine. Isopropanol was added to this powder to make a 500g mixed liquid, and the mixture was dispersed using a high-pressure homogenizer to obtain 500g of conductive polymer-containing liquid. The results of measuring the non-volatile component concentration of this containing liquid are shown in Table 4. Next, the obtained conductive polymer-containing liquid was applied onto a PET film using a #8 bar coater and dried at 100° C. for 1 minute to obtain a conductive film, and its surface resistance was measured. The results are shown in Table 4.
[0174] Comparative Example 13 A conductive polymer-containing liquid containing isopropanol as a dispersion medium was obtained and a conductive film was produced in the same manner as in Example 13, except that 100 g of the conductive polymer-containing liquid of Example 1 was changed to 100 g of the conductive polymer-containing liquid (non-volatile component concentration 1.0 mass%) of Comparative Example 1. The results are shown in Table 4.
[0175] Example 14 25 g of an epoxy compound (Kyoeisha Chemical Co., Ltd., Epolite M-1230, C12,13 mixed higher alcohol glycidyl ether) was added to 100 g of the conductive polymer-containing liquid (non-volatile component concentration 1.0 mass%) of Example 1, and the mixture was heated and stirred at 60°C for 4 hours to react the epoxy compound with some of the sulfonic acid groups of the conductive complex. As a result, a reaction product was precipitated. This precipitate was filtered to obtain a reaction product of the conductive complex and the epoxy compound. Methyl ethyl ketone was added to this reaction product to make a 300 g mixed liquid, and the mixture was dispersed using a high-pressure homogenizer to obtain 300 g of a conductive polymer-containing liquid. The results of measuring the non-volatile component concentration of this liquid are shown in Table 4. Next, the obtained conductive polymer-containing liquid was applied onto a PET film using a #8 bar coater and dried at 100° C. for 1 minute to obtain a conductive film, and its surface resistance was measured. The results are shown in Table 4.
[0176] (Comparative Example 14) A conductive polymer-containing liquid containing methyl ethyl ketone as a dispersion medium was obtained and a conductive film was produced in the same manner as in Example 14, except that 100 g of the conductive polymer-containing liquid of Example 1 was changed to 100 g of the conductive polymer-containing liquid (non-volatile component concentration 1.0 mass%) of Comparative Example 1. The results are shown in Table 4.
[0177] Example 15 25 g of an epoxy compound (Kyoeisha Chemical Co., Ltd., Epolite M-1230, C12,13 mixed higher alcohol glycidyl ether) was added to 100 g of the conductive polymer-containing liquid (non-volatile component concentration 1.0 mass%) of Example 1, and the mixture was heated and stirred at 60 ° C. for 4 hours. Next, 50 g of isopropanol and 10 g of trioctylamine were added and stirred for 1 hour, whereby the epoxy compound and trioctylamine reacted with some of the sulfonic acid groups of the conductive complex. As a result, a reaction product was precipitated. This precipitate was filtered to obtain a reaction product of the conductive complex with the epoxy compound and trioctylamine. Ethyl acetate was added to this reaction product to obtain 800 g of a mixed liquid, which was then dispersed using a high-pressure homogenizer to obtain 800 g of a conductive polymer-containing liquid. The results of measuring the non-volatile component concentration of this liquid are shown in Table 4. Next, the obtained conductive polymer-containing liquid was applied onto a PET film using a #8 bar coater and dried at 100° C. for 1 minute to obtain a conductive film, and its surface resistance was measured. The results are shown in Table 4.
[0178] Comparative Example 15 A conductive polymer-containing liquid containing ethyl acetate as a dispersion medium was obtained, a conductive film was obtained, and its surface resistance was measured in the same manner as in Example 15, except that 100 g of the conductive polymer-containing liquid of Example 1 was replaced with 100 g of the conductive polymer-containing liquid of Comparative Example 1 (non-volatile component concentration 1.0 mass%). The results are shown in Table 4.
[0179] [Table 4]
[0180] <Result> In the above-mentioned molecular weight reduction process, PSS that did not form PEDOT-PSS was reduced in molecular weight by heat treatment, and the surface resistance value of the conductive film formed using the conductive polymer-containing liquid of the example in which the weight average molecular weight ratio (Y / X) was 0.85 or less was superior to the surface resistance value of the conductive film formed using the conductive polymer-containing liquid of the comparative example in which the molecular weight ratio (Y / X) exceeded 0.85.
[0181] <Mechanism of action> It is presumed that by lowering the molecular weight of the single polyanions that do not form conductive complexes, the proportion of the single polyanions present on the surface of the coating film is reduced, and the proportion of the conductive complexes present on the surface is relatively increased, resulting in improved conductivity (surface resistance value) of the conductive layer. On the other hand, in the conductive polymer-containing liquid of the comparative example, the single polyanions remain at a high molecular weight, so the single polyanions tend to gather on the surface of the coating film (they are expelled from the depths and tend to accumulate on the surface), resulting in poor conductivity (surface resistance value) of the conductive layer.
Claims
1. A monomer that forms a π-conjugated conductive polymer is polymerized in a reaction solution containing a polyanion and an aqueous dispersion medium, a polymerization step of obtaining a conductive polymer-containing liquid containing a conductive complex containing the π-conjugated conductive polymer and the polyanion, the aqueous dispersion medium, and the polyanion that does not form the conductive complex; a molecular weight reduction step of reducing the weight average molecular weight of the polyanion that is not forming the conductive complex and is contained in the conductive polymer-containing liquid; A method for producing a conductive polymer-containing liquid, comprising: a molecular weight ratio represented by Y / X of a weight average molecular weight X of the polyanion not forming the conductive complex contained in the conductive polymer-containing liquid subjected to the molecular weight reduction step to a weight average molecular weight Y of the polyanion not forming the conductive complex contained in the conductive polymer-containing liquid after the molecular weight reduction step is 0.85 or less, In the molecular weight reduction step, the conductive polymer-containing liquid (excluding a liquid containing an alkaline compound) is heat-treated at 40° C. or higher and 100° C. or lower for 600 hours or higher and 3,000 hours or lower.
2. The method for producing a conductive polymer-containing liquid according to claim 1 , wherein the molecular weight ratio is 0.60 or more and 0.85 or less.
3. 3. The method for producing a conductive polymer-containing liquid according to claim 1, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid.
4. The method for producing a conductive polymer-containing liquid according to any one of claims 1 to 3, wherein the polyanion is polystyrene sulfonic acid, and the weight average molecular weight Y of the polystyrene sulfonic acid is 50,000 or more and 600,000 or less.
5. 5. The method for producing a conductive polymer-containing liquid according to claim 1, further comprising the steps of: adding an epoxy compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step; and obtaining a conductive polymer-containing liquid containing a reaction product obtained and an organic solvent.
6. The method for producing a conductive polymer-containing liquid according to any one of claims 1 to 4, further comprising adding an amine compound or a quaternary ammonium compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step, thereby obtaining a conductive polymer-containing liquid containing the obtained reaction product and an organic solvent.
7. 5. The method for producing a conductive polymer-containing liquid according to claim 1, further comprising adding an epoxy compound, and an amine compound or a quaternary ammonium compound to the conductive polymer-containing liquid that has been subjected to the molecular weight reduction step, thereby obtaining a conductive polymer-containing liquid containing the obtained reaction product and an organic solvent.
8. A method for producing a conductive laminate, comprising: obtaining a conductive polymer-containing liquid by the production method according to any one of claims 1 to 7; and applying the conductive polymer-containing liquid to at least a part of a surface of a substrate.
9. The method for producing a conductive laminate according to claim 8 , wherein the substrate is a film substrate.
Citation Information
Patent Citations
Method for producing conductive polymer dispersion liquid and method for producing conductive film
JP2017115089A
Conductive polymer composite, conductive polymer-containing solution, method for producing conductive polymer composite, method for producing conductive polymer-containing solution, method for producing conductive film and conductive film
JP2020111650A
Transparent laminate
JP2021014113A
Conductive polymer-containing liquid and method for producing the same, conductive film and method for producing the same, and conductive laminate and method for producing the same
JP2021181544A